CONCEPTUAL PRINCIPLES OF THE CREATION OF THE "UKRAINIAN ELECTRONIC ENCYCLOPEDIA OF EDUCATION" - Bykov, Valeriy; Burov , Oleksandr; Luparenko , Liliia; Pinchuk , Olga; Iatsyshyn , Anna (Physical and Mathematical Education, 2022)
Formulation of the problem. In the scientific and educational space of Ukraine, there is still no single specialized branch digital scientific and educational information and reference system, which would contain freely available encyclopedic scientifically reliable and modern interpretations of the terminology of pedagogy and psychology. In view of this, the design and implementation of the national web-oriented educational encyclopedia becomes especially relevant. Materials and methods. To achieve the goal of the article, an analysis of scientific-methodical and scientific-technical literature, regulatory and legal documentation, current national and international standards on the studied issues was carried out; generalization of domestic and foreign experience of using web-oriented encyclopedias in scientific and pedagogical activities. Results. The article describes the goals, objectives, regulatory and legal basis for the creation of the open "Ukrainian electronic encyclopedia of education". The potential target audience, participants, characteristics, and principles of creating a digital reference resource, types of articles and requirements for them, technical and design concepts are briefly described. The structure and functionality of the site, characteristics of data search tools, ergonomic requirements and stages of project implementation are considered. Conclusions. The designed Internet platform will allow collecting on a single resource a significant conceptual and terminological apparatus of pedagogy and psychology. It will represent the most modern knowledge of educational sciences in a user-friendly format that corresponds to the development of digital technologies and considers the needs of different categories of users. It will feature the most outstanding educators, pedagogues, and psychologists; interpreted phenomena, concepts, and terms; the influence of various institutions, institutions of higher education and organizations on the development of education and psychology is described; the development of views on education, upbringing and psychology and the dynamics of scientific ideas in these fields of knowledge are reflected.